2021
DOI: 10.1016/j.tibs.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Charting a DNA Repair Roadmap for Immunoglobulin Class Switch Recombination

Abstract: Immunoglobulin (Ig) class switch recombination (CSR) is the process occurring in mature B cells that diversifies the effector component of antibody responses. CSR is initiated by the activity of the B cell-specific enzyme activation-induced cytidine deaminase (AID), which leads to the formation of programmed DNA double-strand breaks (DSBs) at the Ig heavy chain (Igh) locus. Mature B cells use a multilayered and complex regulatory framework to ensure that AIDinduced DNA breaks are channeled into productive repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 133 publications
(287 reference statements)
1
34
0
Order By: Relevance
“…Accordingly, EXO1 played vital roles in immunoglobulin maturation and antibody diversity through class switching recombination and somatic hypermutation. 59 , 60 Therefore, aberrant overexpression of EXO1 may result in the dysfunction of immunoglobulin maturation and reduction of antibody diversity, which may further decrease the infiltrating B cell levels. 34 Furthermore, B cell depletion impaired CD4+ T cell activation and clonal expansion in mice whereas CD8+ T cell activation was not affected.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, EXO1 played vital roles in immunoglobulin maturation and antibody diversity through class switching recombination and somatic hypermutation. 59 , 60 Therefore, aberrant overexpression of EXO1 may result in the dysfunction of immunoglobulin maturation and reduction of antibody diversity, which may further decrease the infiltrating B cell levels. 34 Furthermore, B cell depletion impaired CD4+ T cell activation and clonal expansion in mice whereas CD8+ T cell activation was not affected.…”
Section: Discussionmentioning
confidence: 99%
“…In the regard, in B cell deficient for cNHEJ factors, CSR efficiency dramatically decreased to 30% of that of wild‐type (WT) cells but is not completely abolished, suggesting the existence of alternative pathway (A‐EJ) in the absence of c‐NHEJ 17–20 . AID‐initiated DSBs also activate ATM‐dependent DDR process, and it has been clear in literatures that mature B cells deficiency for ATM and its downstream substrates H2AX, 53BP1, Rif1, and so on, significantly reduced CSR efficiency with elevated DSB end resection and use of short sequence homology in joining junctions 16,19,21,22 . Meanwhile, prior studies had suggested that stimulated Lig4‐deficient B cells exhibited elevated S region 5â€Č−3â€Č DSB resection that exposes single‐stranded overhang DNA for microhomology (MH) annealing 21 .…”
Section: Introductionmentioning
confidence: 99%
“…CSR replaces the initially expressed IgM molecules on mature B cells with one of the IgG/IgE/IgA constant region exons 12,13 . It is initiated by activation‐induced cytosine deaminase (AID)‐introduced DNA lesions in donor and acceptor long repetitive switch (S) regions (Sm and Sx respectively) that are subsequently converted to DSBs, and completed by the rejoining of DSBs by the core NHEJ factors Xrcc4/Ligase4 with assistance from the Ku70/80 complex and DNA‐PKcs to hold broken ends from falling apart 14–16 . In the regard, in B cell deficient for cNHEJ factors, CSR efficiency dramatically decreased to 30% of that of wild‐type (WT) cells but is not completely abolished, suggesting the existence of alternative pathway (A‐EJ) in the absence of c‐NHEJ 17–20 .…”
Section: Introductionmentioning
confidence: 99%
“…At the molecular level, CSR is mediated by a deletional recombination reaction at the Ig heavy chain locus (Igh) that replaces the constant (C) gene for the basal IgM isotype with one of the downstream C genes encoding a different Ig class (Yewdell and Chaudhuri, 2017). The reaction is initiated by the formations of multiple programmed DSBs at internally repetitive DNA stretches, known as switch (S) regions, preceding the recombining C regions (Saha et al, 2021). Productive CSR events occur via protection of DSBs from nucleolytic resection, which enables NHEJ-mediated inter-S-region repair (Boboila et al, 2012;Saha et al, 2021).…”
Section: Introductionmentioning
confidence: 99%